2021
DOI: 10.3390/ijerph182312422
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Effects of Government Response on the COVID-19 Infection Rate in China: A Multiple Mediation Analysis

Abstract: Many scholars have considered the relationship between the government response to COVID-19, an important social intervention strategy, and the COVID-19 infection rate. However, few have examined the sustained impact of an early government response on the COVID-19 infection rate. The current paper fills this gap by investigating a national survey performed in February 2020 and infection data from Chinese cities surveyed 1.5 years after the outbreak of COVID-19. The results suggest that the Chinese government’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Public risk perception (RP) changes with time, which is an important consideration in public health emergencies and risk management decision-making ( 3 ), while its role can be easily overlooked in the construction of emergency management systems. RP is defined as the subjective judgment people make about the characteristics and severity of risks ( 4 ), which was likely to be influenced by many factors like personal characteristics, health literacy during a crisis such as the COVID-19 pandemic ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Public risk perception (RP) changes with time, which is an important consideration in public health emergencies and risk management decision-making ( 3 ), while its role can be easily overlooked in the construction of emergency management systems. RP is defined as the subjective judgment people make about the characteristics and severity of risks ( 4 ), which was likely to be influenced by many factors like personal characteristics, health literacy during a crisis such as the COVID-19 pandemic ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Public risk perception (RP) is defined as the subjective judgment people make about the characteristics and severity of risks [ 35 ], which is an essential consideration in public health emergencies and risk management decision-making [ 36 ]. A qualitative study revealed that people influenced by information and advice campaigns perceive a risk that has shaped their protective behavior [ 10 ].…”
Section: Literature Review and Analysis Frameworkmentioning
confidence: 99%
“…Although several effective vaccines against the virus have been developed to date [3], nations are still applying previous control guidelines made to control the spread of SARS-CoV-2 [4,5]. Protective measures include social exclusion, closure of educational institutions, restrictions on events and social gatherings, regulations on the use of personal protective equipment (especially masks), travel restrictions, border closures and ongoing testing [6][7][8]. In addition, some nations have declared a state of emergency and introduced a partial lockdown to control the current third wave [9,10], which has restricted the movement of people and thus has an impact on the world of work [11][12][13].…”
Section: Introductionmentioning
confidence: 99%